Optimizing Pedagogy through Gamification: A Scientific Approach to Enhancing Student Motivation in Madrasah - Faizin Faizin; Moh Fachri; Muhammad Munif (Universitas Nurul Jadid, 2024)
This research focuses on optimizing pedagogy through gamification as a scientific approach to increasing student motivation in madrasas. This research aims to analyze the effectiveness of gamification elements in the learning process and how this can influence student motivation and engagement. This research uses a qualitative method with a case study approach, where data is collected through in-depth interviews, class observations, and content analysis. Research findings show that implementing gamification significantly increases student motivation, primarily through the dynamic engagement generated by game elements such as challenges, point systems, and rewards. Students who engage in gamification-based learning show increased active participation and a greater desire to achieve academic goals. The implications of this research highlight the importance of integrating appropriate gamification elements in madrasa curricula to create a more interactive and motivating learning environment and the challenges that need to be considered regarding adapting gamification to diverse learning styles.